2011
DOI: 10.2215/cjn.07130810
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure in Long-Term Peritoneal Dialysis Patients

Abstract: SummaryBackground and objectives Heart failure occurs frequently in end-stage renal disease patients. However, there are no prospective, longitudinal follow-up data on its prevalence, severity, and risk factors in longterm peritoneal dialysis (PD) patients.Design, setting, participants, & measurements A prospective observational study was conducted in 220 longterm PD patients followed up for 4 years or until death. Echocardiography was obtained at baseline. Primary study end points were heart failure and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Many studies have shown that diastolic dysfunction may ultimately be a risk factor for LV systolic dysfunction and future congestive heart failure [20]. We also found that none of our patients had congestive heart failure and all had normal systolic function despite increased LV mass index, though with a significantly better LV systolic function after 18 months of PD treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Many studies have shown that diastolic dysfunction may ultimately be a risk factor for LV systolic dysfunction and future congestive heart failure [20]. We also found that none of our patients had congestive heart failure and all had normal systolic function despite increased LV mass index, though with a significantly better LV systolic function after 18 months of PD treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Heart failure (HF) is one of the most frequent cardiac complications in ESRD patients. Left ventricular (LV) systolic dysfunction, defined by low LV ejection fraction (LVEF), is associated with poor prognosis (2)(3)(4). However, abnormal LV functions, as recognized by conventional echocardiography, may identify only dialysis patients with established cardiovascular disease (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] But there are no clear-cut criteria for the diagnosis of hypovolemia or hypervolemia. Some patients have elevated systolic blood pressure, despite being euvolemic which is thought to be due to vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…For both the treatment modalities, international guidelines underline volume status for dialysis adequacy. 1 One of the main factors determining the morbidity and mortality in PD patients is volume status [2][3][4][5][6][7] and may even be more important than solute clearance. 8 Besides clinical findings (blood pressure, presence of edema, and weight gain), echocardiography, Dual Energy X-ray Absorptiometry (DEXA), direct measurement of extracellular and total body water (TBW), brain natriuretic peptide (BNP) has been used for the determination of hydration status.…”
Section: Introductionmentioning
confidence: 99%